Stenotrophomonas strain CD2 reduces cadmium accumulation in Brassica rapa L. - Fan, Xia; Yuan, Kai; Peng, Qian; Lv, Ruiling; Zheng, Yongliang (Frontiers in Sustainable Food Systems, 2024)
Cadmium (Cd) is a highly toxic heavy metal which contaminates agricultural soils and is easily absorbed by plants. Brassica rapa L. is one of the most popular vegetables in China and is known to accumulate Cd in its roots and aerial tissues. In this study, a highly Cd-resistant bacterium (‘CD2’) was isolated and classified as belonging to the genus Stenotrophomonas. Strain CD2 was found to be able to remove 0.1 mmol/L Cd(II) after 36 h by intracellular sequestration and by producing biofilm, exopolysaccharide, and H2S. When applied to Cd-contaminated soil, ‘CD2’ significantly increased the content of nonbioavailable Cd by 212.70%. Furthermore, ‘CD2’-inoculated B. rapa exhibited a 51.16% decrease in the Cd content of roots and a 55.56% decrease in the Cd content of aerial tissues. Transcriptome analysis identified 424 differentially expressed genes (DEGs) in the roots and 501 DEGs in the aerial tissues of uninoculated Cd-exposed plants. By comparison, 1107 DEGs were identified in the roots and 1721 DEGs were identified in the aerial tissues of ‘CD2’-inoculated Cd-exposed plants. In both treatment groups, genes related to vacuolar sequestration were upregulated, resulting in inhibited Cd transport. In addition, both catalase and glutathione transferase were induced in uninoculated plants, while the oxidative stress-related genes CPK and RBOH belonged to ‘plant-pathogen interactions’ were upregulated in ‘CD2’-inoculated plants. Moreover, inoculation with ‘CD2’ resulted in the enrichment of phenylpropane metabolism; cutin, suberine, and wax biosynthesis; and the AP2, Dof, WOX, Trihelix, B3, EIL, and M-type_MADS transcription factors; as well as the downregulation of zinc transporters and blue copper proteins. All of these changes likely contributed to the reduced Cd accumulation in ‘CD2’-inoculated B. rapa. The results of this study suggest that Stenotrophomonas sp. CD2 may prove to be a useful inoculant to prevent Cd accumulation in B. rapa.